The Role of the Work Environment in Moderating the Effect of Transformational Leadership Style, Competence, and Teamwork on Nurse Performance at the Alodia Kolaka Clinic - Adinda Putri, Paramita; Putriani, Dewi (Dinasti Publisher, 2024)
This study aims to determine the role of the work environment in moderating the influence of transformational leadership style, competence, and teamwork on nurse performance. The research approach uses a quantitative method with an associative type. The sample of this study was nurses at the Alodia Clinic, Kolaka, Southeast Sulawesi. The data analysis technique used the Structural Equation Model - Partial Least Square (SEM-PLS) using the Smart PLS program version 3.2.9. The results showed that transformational leadership style influenced nurse performance. Competence influences nurse performance. Teamwork influences nurse performance. The work environment cannot moderate the influence of transformational leadership style, competence, and teamwork on nurse performance at the Alodia Clinic, Kolaka, Southeast Sulawesi.